C:N:P stoichiometry in plant, soil and microbe in Sophora moorcroftiana shrubs across three sandy dune types in the middle reaches of the Yarlung Zangbo River - Dong, Ruizhen; Yang, Shihai; Wang, Xiaoli; Xie, Lele; Ma, Yushou; Wang, Yanlong; Zhang, Litian; Zhang, Min; Qin, Jinping (Frontiers in Plant Science, 2023)
The alpine sandy dune ecosystem is highly vulnerable to global climate change. Ecological stoichiometry in plants and soils plays a crucial role in biogeochemical cycles, energy flow and functioning in ecosystems. The alpine sandy dune ecosystem is highly vulnerable to global climate change. However, the stoichiometric changes and correlations of plants and soils among different types of sandy dunes have not been fully explored. Three sandy dune types (moving dune, MD; semifixed dune, SFD; and fixed dune, FD) of the Sophora moorcroftiana shrub in the middle reaches of the Yarlung Zangbo River were used as the subjects in the current study. Plant community characteristics, soil physicochemical properties, carbon (C), nitrogen (N), and phosphorus (P) contents of leaves, understorey herbs, litter, and soil microbes were evaluated to explore the C:N:P stoichiometry and its driving factors. Sandy dune type significant affected on the C:N:P stoichiometry in plants and soils. High soil N:P ratio was observed in FD and high plant C:P and N:P ratios in SFD and MD. The C:N ratio decreased with sand dune stabilization compared with other stoichiometric ratios of soil resources. Leaf C:P and N:P ratios in S. moorcroftiana were higher than those in the understorey herb biomass, because of the low P concentrations in leaves. C, N and P contents and stoichiometry of leaves, understorey herbs, litter and microbe were significantly correlated with the soil C, N and P contents and stoichiometry, with a higher correlation for soil N:P ratio. P was the mainly limiting factor for the growth of S. moorcroftiana population in the study area and its demand became increasingly critical with the increase in shrub age. The variation in the C:N:P stoichiometry in plants and soils was mainly modulated by the soil physicochemical properties, mainly for soil moisture, pH, available P and dissolved organic C. These findings provide key information on the nutrient stoichiometry patterns, element distribution and utilization strategies of C, N and P and as well as scrubland restoration and management in alpine valley sand ecosystems.